Antifungal activity of boric acid, triclosan and zinc oxide against different clinically relevant Candida species (2021)
ABSTRACT: Background: The genus Candida includes about 200 different species, but only a few are able to produce disease in humans. The species responsible for the highest proportion of human infections is Candida albicans. However, in the last two decades there has been an increase in the proportion of infections caused by other Candida species, including C. glabrata (Nakaseomyces glabrata), C. parapsilosis, C. tropicalis, C. krusei (Pichia kudriavzevi) and more recently C. auris. Decolonisation of patients has been used as an infection control strategy for bacterial infections, but information about decolonisation products used in clinical practice for Candida and other fungal pathogens is limited. Compounds with antimicrobial activity, such as triclosan (TR), boric acid (BA) and zinc oxide (ZO), are mainly used in personal care products. These products can be used for long periods of time without an abrasive skin effect and are a possible alternative for patient decolonisation in healthcare settings. Objective: The aim of this study was to evaluate the antifungal activity of boric acid (BA), triclosan (TR) and zinc oxide (ZO), individually and combined, against clinically relevant Candida species. Materials and methods: Compounds to be screened for antifungal activity were evaluated at different concentrations, alone, and combined, using a well diffusion assay. The statistical evaluation was performed using analysis of variance (ANOVA) and a post hoc analysis using the multiple comparisons method. Results: Individually, BA and TR showed antifungal activity against all Candida species evaluated but ZO did not show any antifungal activity. Mixtures of BA [5%]-TR [0.2%]; BA [5%]-TR [0.3%]; BA [5%]-TR [0.2%]-ZO [8.6%]; and BA [5%]-TR [0.2%]-ZO [25%] yielded the highest antifungal activity. An increased antifungal effect was observed in some mixtures when compared with individual compounds. Conclusions: We demonstrated antifungal activity of BA and TR against multiple Candida species, including against a clade of the emerging healthcare-associated pathogen C. auris. Additionally, this study shows enhancement of the antifungal effect and no antagonism among the mixtures of these compounds. Further research is needed to determine whether these compounds can reduce the burden of Candida on skin.